The Effectiveness of Art Therapy as a Therapeutic Method in Reducing Children's Mental Trauma in Broken Home Adolescents - Syam, Rahmawati; Aulia Q. Jamil, Nafizah; Hasrinatha Tahir, Firza Soelistina; Febriani, Putri (Polteknik Ilmu Pemasyarakatan, 2023)
Divorce cases that occur in Indonesia continue to increase every year. This divorce not only has an impact on husband and wife, but there are people who are more affected, namely children. Children who are victims of divorce are often labeled as children from broken homes. Children who often witness their parents arguing, are neglected, receive less love and protection can have an impact on the emergence of emotional wounds which give rise to inner child trauma which, if not addressed immediately, will have an impact on the child's condition as an adult. This research aims to determine the effectiveness of art therapy in reducing inner child trauma in broken home teenagers. The method used is art therapy. Art therapy is a form of psychotherapy that uses art media as a medium for catharsis, emotional ventilation, getting to know oneself better through art media, being able to express oneself and explore life patterns effectively. Participants in this research were 3 teenagers who experienced a broken home. This intervention consists of 10 sessions. The results of this research show that the Z value obtained is -2.041 with a p-value (Asymp. Sig 2 tailed) of 0.041 < 0.05. So it can be interpreted that the alternative hypothesis (H1) states that there is a significant difference between the pretest and posttest groups. The conclusion in this research is that trauma to an individual's inner child can have a long-term impact so that treatment is needed, in this case the researcher used the Art Therapy method as an effort to reduce inner child trauma in broken home teenagers.